2021
DOI: 10.1186/s12864-021-08006-1
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genomes of five Oedogonium species: genome structure, phylogenetic analysis and adaptive evolution

Abstract: Background The order Oedogoniales within the single family Oedogoniaceae comprised of three genera, Oedogonium, Oedocladium, and Bulbochaete based on traditional morphological criteria. While several molecular phylogenetic studies have suggested that both Oedogonium and Oedocladium may not be monophyletic, broader taxon sampling and large amounts of molecular data acquisition could help to resolve the phylogeny and evolutionary problems of this order. This study determined five chloroplast (cp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…Based on both the GO enrichment and KEGG pathway analyses, the function of the putative rapidly evolving genes is related to photosynthesis, considering the differences between aquatic and terrestrial habitats, we speculated that the terrestrial Oedogoniales species underwent rapid evolution to adapt to the varying conditions, especially for the terrestrialization process. This observation is consistent with the findings of a previous study that was based on chloroplast protein-coding genes [22]. A previous study revealed that the transition from water to land occurred several times and across different taxa, ranging from microorganisms to lichens and green plants, and later, arthropods, mollusks, annelids, and vertebrates [84].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on both the GO enrichment and KEGG pathway analyses, the function of the putative rapidly evolving genes is related to photosynthesis, considering the differences between aquatic and terrestrial habitats, we speculated that the terrestrial Oedogoniales species underwent rapid evolution to adapt to the varying conditions, especially for the terrestrialization process. This observation is consistent with the findings of a previous study that was based on chloroplast protein-coding genes [22]. A previous study revealed that the transition from water to land occurred several times and across different taxa, ranging from microorganisms to lichens and green plants, and later, arthropods, mollusks, annelids, and vertebrates [84].…”
Section: Discussionsupporting
confidence: 92%
“…The phylogenetic results based on the three kinds of dataset (18S rDNA, 99/29 singlecopy orthologues based on Oedogoniales and the OCC clade respectively) showed the same results that Oedogonium was polyphyletic and Oedocladium species formed a separate clade clustering with Oedogonium. At the same time, with C. reinhardtii as an outgroup, a BI tree based on 99 single-copy orthologues determined by the supermatrix method showed results similar to those of the ST analyzed by ASTRAL, which is consistent with the phylogenetic results based on 18S rDNA sequences, internal transcribed spacers (ITS), and chloroplast protein coding genes [21,22]. The inconsistency in the results observed with regard to the position of Oe.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The parameters in CODEML control file were set as follow: (1) F3 × 4 model for codon frequencies; (2) “model = 0” for allowing a single dN/dS value to vary among branches; (3) “cleandata = 1” to remove gaps; (4) default settings for other parameters (as alternative model, “fix_omega = 0” and “omega = 2”) [ 64 ]. For the potential positive selection gene, a null model (set “fix_omega = 1” and “omega = 1” in the control file) was additionally performed following Xiong et al [ 93 ]. LRT were used to test model fit and a Chi-square test was conducted to calculate the P value.…”
Section: Methodsmentioning
confidence: 99%